Relationship between HbA1c levels and coronary artery severity in nondiabetic acute coronary syndrome patients - Ahmet Göktuğ ERTEM; Hüseyin Bağbancı; Harun Kılıç; Ekrem Yeter; Ramazan Akdemir (KARE Publishing, 2013)
Objectives: In this study, we aimed to investigate the relationship between HbA1c levels and the severity of coronary artery stenosis in patients with acute coronary syndrome (ACS) without diabetes mellitus. Study design: In this study, we included 65 patients (11 females, mean age: 57+-11.42 years; 54 males, mean age: 54.56+-8.51 years) who were diagnosed as acute myocardial infarction without diabetes mellitus. During hospitalization, fasting blood glucose, postprandial blood glucose and HbA1C were measured in each patient. Gensini score was used to assess the severity of coronary artery disease. Results: Twenty patients (30.8%) had hypertension, 15 (23.1%) had impaired fasting glucose, 10 (15.3%) had combined impaired fasting and postprandial glucose, 28 had a low HDL cholesterol (45%), and 30 (46%) had abdominal obesity. Coronary angiography revealed one-vessel disease in 13 patients (20%), and two- and three-vessel disease in 52 patients (80%). There were no significant differences in terms of high-sensitive C-reactive protein (hs-CRP), total cholesterol, fasting glucose, and postprandial glucose (0.068, 0.974, 0.178, 0.677, respectively). There was no significant relation between the Gensini score and HbA1c levels (p=0.299), but there was a significant relation between the Gensini score and obesity (p=0.024). Conclusion: In our study, no significant relationship could be determined between the Gensini score and HbA1C, fasting and postprandial blood glucose levels, lipid profile, and hs-CRP levels in patients with nondiabetic ACSs